Tolerability and safety of artesunate-amodiaquine and artemether-lumefantrine fixed dose combinations for the treatment of uncomplicated Plasmodium falciparum malaria: two open-label, randomized trials in Nimba County, Liberia - Schramm, Birgit (BioMed Central, 2013)
BACKGROUND: Safety surveillance of widely used artemisinin-based combination therapy (ACT) is essential, but tolerability data in the over five years age group are largely anecdotal. METHODS: Two open-label, randomized trials were conducted in Nimba County, Liberia: i) the main tolerability trial with 1,000 Plasmodium falciparum malaria patients aged over five years (Study-T), and, ii) an efficacy trial with a secondary objective of collecting tolerability data among 300 children age six to 59 months (Study-E). In both studies patients were randomized to fixed-dose artesunate-amodiaquine (ASAQ Winthrop®) or artemether-lumefantrine (AL, Coartem®), respectively. Clinical- and laboratory-adverse events (AEs) were recorded until day 28. RESULTS: Study-T: most patients experienced at least one AE. Severe AEs were few, primarily asymptomatic blood system disorders or increased liver enzyme values. No treatment or study discontinuation occurred. Mild or moderate fatigue (39.8% vs 16.3%, p < 0.001), vomiting (7.1% vs 1.6%, p < 0.001), nausea (3.2% vs 1.0%, p = 0.01), and anaemia (14.9% vs 9.8%, p = 0.01) were more frequently recorded in the ASAQ versus AL arm. Study-E: mild or moderate AEs were common, including anaemia, fatigue, vomiting or diarrhoea. The few severe events were asymptomatic blood system disorders and four clinical events (pneumonia, malaria, vomiting and stomatitis). CONCLUSION: Both ASAQ and AL were well tolerated in patients of all age groups. No unexpected AEs occurred. Certain mild or moderate AEs were more frequent in the ASAQ arm. Standardised safety surveillance should continue for all forms of ACT. TRIAL REGISTRATION: The protocols were registered with Current Controlled Trials, under the identifier numbers ISRCTN40020296, ISRCTN51688713, (http://www.controlled-trials.com).